Novel Turbulence Absorption Technique for Enhancing the Liquids Flow in Pipelines - Abdulbari, Hayder A.; R. M., Yunus; Ashwin Charles, Benedict (2014)

(untitled)
In the present work, an new technique for enhancing the flow in pipelines is introduced. Such technique depends on inserting Turbulence Absorbing Unit, TAU with certain dimensions inside the pipe. This unit was designed to absorb and redirect the turbulent structures inside the pipelines. Liquid circulation system with a testing section divided into four subsections was fabricated and used to test the drag reduction effect of the new technique. The results showed that almost 30% flow enhancement is achievable when inserting 12 strips with 20cm length into 0.0381 m diameter pipe.